The Influence of Transformational Leadership on Lecturer Commitment Which Has Implications For Lecturer Performance at Private Universities in The East Priangan Region - Jaenudin, Ujang Eri; Priadana, HM Sidik; Juniarti, Atty Tri (Journal of Business Management Education (JBME), 2024)
The value of educational success is highly dependent on the quality of the teachers. Lecturers are people who play a very important role in the teaching and learning process. Lecturers are also the most important parameter in the process of controlling higher education institutions, especially in private universities. The causal study research method was through a survey with a questionnaire containing closed statements to 234 lecturers in the East Priangan region who were randomly selected. Data analysis uses path analysis. The results of the study show that Transformational Leadership has an effect on Lecturer Commitment and has implications for Lecturer Performance at Private Universities in the East Priangan Region.